2018
DOI: 10.1038/s41419-018-0567-0
|View full text |Cite|
|
Sign up to set email alerts
|

Autophagic degradation of caveolin-1 promotes liver sinusoidal endothelial cells defenestration

Abstract: Autophagy, interacting with actin cytoskeleton and the NO-dependent pathway, may affect the phenotype and function of endothelial cells. Moreover, caveolin-1 (Cav-1), as a structure protein in liver sinusoidal endothelial cells (LSECs), is closely related to autophagy. Hence, we aim to explore the role of autophagic degradation of Cav-1 in LSECs defenestration. In vivo, we found the increase of autophagy in liver sinusoidal endothelium in human fibrotic liver. Furthermore, autophagy, degradation of Cav-1, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 35 publications
(45 reference statements)
4
41
0
Order By: Relevance
“…Moreover, autophagy drives HSC activation by generating metabolic homeostasis. 41,44 In fact, in ours results we demonstrated that GRX EGFP-Cav1 cells endocytosed more FluorSpheres® when compared with GRX. Importantly, Cav-1 and its interactions with actin cytoskeleton and ATP play a pivotal role in the structure, formation, and function of caveolae.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Moreover, autophagy drives HSC activation by generating metabolic homeostasis. 41,44 In fact, in ours results we demonstrated that GRX EGFP-Cav1 cells endocytosed more FluorSpheres® when compared with GRX. Importantly, Cav-1 and its interactions with actin cytoskeleton and ATP play a pivotal role in the structure, formation, and function of caveolae.…”
Section: Discussionsupporting
confidence: 50%
“…Cav‐1 has an extensive membrane distribution in all organelles, including lysosomes. Moreover, autophagy drives HSC activation by generating metabolic homeostasis …”
Section: Discussionmentioning
confidence: 99%
“…The contraction and dilatation of fenestrae in HSECs and its differentiation are regulated by actin cytoskeleton (including F-actin) [4]. Our previous studies reveal that oxidative stress facilitates defenestration in HSECs via F-actin remodeling in liver fibrogenesis [5,6]. Novel findings show that lamins and their associated proteins, which regulate nucleoskeleton and cytoskeleton, affect cellular differentiation and senescence [7,8].…”
Section: Introductionmentioning
confidence: 95%
“…Primary rat HSECs were isolated from normal male SD rats and identified by SEM, based on the modified method [5,6]. Primary rat HSECs were cultured in plates with medium comprising 80% MCDB131 (Gibco, 10372019) and 20% fetal bovine serum (FBS, Biological Industries, 04-007-1A).…”
Section: Cell Isolation Identification Culture and Treatmentmentioning
confidence: 99%
“…Conflicting results have been obtained regarding the effects of autophagy on LSEC phenotypes and functions. Luo et al reported that autophagy increases in LSECs in human fibrotic livers [52]. In mouse model of fibrosis, the autophagic degradation of caveolin-1, F-actin remodeling, and the downregulation of the nitric oxide (NO)-dependent pathway occur during the process of CCL 4 -induced LSEC defenestration.…”
Section: Liver Sinusoidal Endothelial Cellsmentioning
confidence: 99%